The issue of conception of psychic life in historical aspect - Sańko, Dariusz (Studia Ecologiae et Bioethicae, 2005)
The history of human thoughts since the time of Ancient Greece until present time shows us abundance of thoughts regarding phenomena human psychological life. It is possible to distinguish in this history five mains concepts of psychological life: 1. Ontological concept (psychological life is connected with a soul, which existence is treated as a being); 2. Subjectivistic concept (psychological life is connected with a consciousness); 3. Objectivistic concept (psychological life is connected with behaviour, which can be objective visible for a researcher); 4. Subconsciousnessal concept (psychological life is connected with a subconsciousness); 5. Realistic concept (psychological life is connected with a personality). Looking on issues concepts of psychological life in historical aspect it is possible to see huge abundance of ideas regarding this problem. Each epoch has been trying to resolve of the mystery of human psychological life on measure its own time. These researches made the important footstep in our history, without which, it would not be possible far progress in the discovering of the phenomena psychological life